Fishurdah-ʹi bayānīyah-ʹi Babrak Kārmal dar palīnūm-i chahārdahum-i kumītah-i Markazī-i Ḥizb-i Dimūkrātik-i Khalq-i Afghānistān - Karmal, Babrak ([s.n.], 1984)
Speech delivered by the former president of Afghanistan in the 14th session of the People's Democratic Party of Afghanistan.